Recent Advances on Lignocellulosic-Based Nanopesticides for Agricultural Applications - Lima, Pedro Henrique Correia de; Antunes, Débora Ribeiro; Forini, Mariana Monteiro de Lima; Pontes, Montcharles da Silva; Mattos, Bruno Dufau; Grillo, Renato (Frontiers in Nanotechnology, 2021)
Controlled release systems of agrochemicals have been developed in recent years. However, the design of intelligent nanocarriers that can be manufactured with renewable and low-cost materials is still a challenge for agricultural applications. Lignocellulosic building blocks (cellulose, lignin, and hemicellulose) are ideal candidates to manufacture ecofriendly nanocarriers given their low-cost, abundancy and sustainability. Complexity and heterogeneity of biopolymers has posed challenges in the development of nanocarriers; however, nowadays the engineering toolbox for biopolymer modification has increased remarkably, which enables better control over their properties and tuned interactions with cargoes and plant tissues. In this minireview, we explore the recent advances toward lignocellulosic-based nanocarriers for the controlled release of agrochemicals. Also, we offer a critical discussion regarding the future challenges of this potential bio-based nanocarrier for sustainable agricultural development.